(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
This article presents the origins and structure of German surnames in the Old Town Braniewo in the 15th century. The author verified the presence of the preposition “von”, surname variants, Lower German roots, and evident linguistic phenomena which occurred in them. The discussed surnames are derived from first names, place of origin, nicknames and the names of occupations. Other names are multi-motif surnames, or it was impossible to explain their etymology. As for the structure of the described anthroponyms, non-derivative surnames predominate. Only in the case of one surname were variants recorded. Middle Low German and Lower German provenance is present in about 25% of the examined anthroponyms. In some surnames, manifestations of the East Central German dialect are visible. Several anthroponyms have been Polonised, and one was subject to a contraction.